Disparities in receipt of financial assistance for patients prescribed oral anti-cancer medications at an integrated specialty pharmacy. Issue 28 (1st October 2022) - Ragavan, Meera Vimala; Swartz, Scott; Clark, Mackenzie; White, Jared; Lo, Mimi; Gupta, Arjun; Lin, Tracy Kuo; Chino, Fumiko
Abstract : 217 Background: An increasing number of patients with cancer are prescribed oral anti-cancer medications and face significant challenges in affording them. Financial assistance programs may be a critical resource to mitigate this financial burden but there are often barriers to accessing them. This study evaluated factors associated with receipt of financial assistance among patients with cancer prescribed oral anti-cancer medications. Methods: We conducted a retrospective cohort study including all patients prescribed an oral anti-cancer therapy through the University of California, San Francisco (UCSF) Specialty Pharmacy between January 1, 2021 and December 31, 2021. The unit of analysis was patient-drug. Information on financial assistance, including sponsor, type, and amount secured was extracted through Vivor – a financial navigation and grant tracking tool – and linked to clinical and prescription data extracted from the institutional electronic medical record. We employed a multivariate logistic regression analysis to identify variables associated of receipt of financial assistance.Results: Of 1, 357 unique patient/drug combinations, 488 (36%) received some form of financial assistance. Mean age of patients was 67 years (SD = 14, range 21-97). Patients were predominantly male (69%), lived in an urban area (42%), were retired (41%), and identified as Non-Hispanic White (61%). A minority of patients (13%) were non-English speaking. The most common type of assistance received was from a foundation (35%), followed by free drug program (24%) and copayment card (23%). Healthwell Foundation (28%) and Patient Access Network Foundation (26%) were the most common sponsors for foundation-based support. Receipt of assistance varied (Χ2 = 60.8, p < 0.001) by disease state. Multivariate logistic regression indicated that patients who identified as Hispanic/Latinx ethnicity (OR 0.49, p = 0.038) or were non-English speaking (OR 0.38, p = 0.015) were less likely to receive financial assistance. Conclusions: There were disparities in receipt of financial assistance by ethnicity and primary language spoken. Some patients may not be equitably connected to existing financial resources and may be disproportionately at risk for the financial, clinical, and psychosocial implications of a high out-of-pocket cost burden. Future studies should develop and implement standardized workflows to ensure equitable access to existing financial resources for patients with cancer.